Computer aided optimal design of high power density EMI filters - Ala, G.; Giaconia, G.C.; Giglia, G; Di Piazza, M.C.; Luna, M.; Vitale, G.; Zanchetta, Pericle (2016)
Power density of power converter systems is becoming an increasing crucial design constraint for a wide range of technical applications. Size reduction of EMI filter in power converters is an important challenge due to its significant impact on the overall converter volume and weight. In order to take on this issue, a computer aided procedure for a fast selection of optimal discrete EMI filter components and layout is described in this paper. The proposed technique is a rule-based automatic procedure based on a suitable database that considers the commercially available data sheets of passive components (e.g. magnetic cores, capacitors). It allows the minimization of the filter’s volume and therefore the improvement of the converter’s power density. The size and the performance of an EMI filter designed by using the proposed procedure, have been compared with those of a conventionally designed one. The comparison demonstrates the effectiveness of the proposed method.